Sentiment Analysis of Citayam Fashion Week Phenomenon Using Support Vector Machine - Muhammad Rosyadi; Erlin (UIR PRESS, 2023)
Citayam Fashion Week is a phenomenon that displays a model doing a fashion show using distinctive and unique clothing when crossing a zebra cross as a catwalk. This phenomenon has received extraordinary attention and discussion from various circles and led to numerous pros and cons among the public and observers of society in Indonesia. Therefore, it is great importance to conduct the study on sentiment analysis of this phenomenon to determine society's sentiment tendency to provide government references and help decision-makers improve their policies. Sentiment analysis was performed using the Support Vector Machine based on the polynomial kernel. The results shows that the accuracy, recall, precision and F1-Score value of 95.61%, 95.66%, 96% and 95.55%, respectively. This study proved that the Support Vector Machine classifier with the polynomial kernel provides higher algorithm performance on text classification. Therefore, the government can use the result of this study to evaluate the existence of the citayam fashion week which may be followed by other phenomena.